Investigational drugs currently in phase II clinical trials for actinic keratosis. (3rd July 2019) - Lozzi, Flavia; Lanna, Caterina; Mazzeo, Mauro; Garofalo, Virginia; Palumbo, Vincenzo; Mazzilli, Sara; Diluvio, Laura; Terrinoni, Alessandro; Bianchi, Luca; Campione, Elena
ABSTRACT: Introduction : Actinic keratoses (AKs) are limited areas of irregular epidermal growth on a background of excessive solar exposure. The entire sun-damaged skin is considered a field of cancerization with multiple visible and subclinical lesions. AK management requires field-directed therapies to block lesion relapse and prevent squamous cell carcinoma (SCC). Areas covered : In this review, we focused on phase II clinical trials for AKs, involving well-known agents and newer molecules such as proapoptotic drugs (VDA-1102, SR-T100, oleogel-S10, ICVT, eflornithine), immunomodulants (isotretinoin, tretinoin) and chemopreventive agents (nicotinamide, perillyl alcohol, liposomal T4N5). We used the website 'ClinicalTrials.Gov' as main reference. We selected and discussed completed and ongoing trials and analysed chemical structure and mechanism of action of the investigated molecules. Expert opinion : AK therapy should be tailored on the patient's profile considering first of all the age and site of the AKs, which are relevant parameters for local immune response. The new molecules could be combined to obtain a synergic effect blocking the different steps of skin tumorigenesis. Phase II trials highlight a new therapeutic opportunity to block selectively cell proliferation regulators and work both on the field of cancerization and on the AKs currently present. Trial registration: ClinicalTrials.gov identifier: NCT02239679. Trial registration: ClinicalTrials.gov identifier: NCT01475955. Trial registration: ClinicalTrials.gov identifier: NCT01458587. Trial registration: ClinicalTrials.gov identifier: NCT02632110. Trial registration: ClinicalTrials.gov identifier: NCT02628236. Trial registration: ClinicalTrials.gov identifier: NCT00002975. Trial registration: ClinicalTrials.gov identifier: NCT02799030. Trial registration: ClinicalTrials.gov identifier: NCT02149342. Trial registration: ClinicalTrials.gov identifier: NCT01583816. Trial registration: ClinicalTrials.gov identifier: NCT01998984. Trial registration: ClinicalTrials.gov identifier: NCT01820260. Trial registration: ClinicalTrials.gov identifier: NCT01803477. Trial registration: ClinicalTrials.gov identifier: NCT00852137. Trial registration: ClinicalTrials.gov identifier: NCT00239135. Trial registration: ClinicalTrials.gov identifier: NCT00700063. Trial registration: ClinicalTrials.gov identifier: NCT00375739. Trial registration: ClinicalTrials.gov identifier: NCT00107965. Trial registration: ClinicalTrials.gov identifier: NCT00427050. Trial registration: ClinicalTrials.gov identifier: NCT00544297. Trial registration: ClinicalTrials.gov identifier: NCT01358851. Trial registration: ClinicalTrials.gov identifier: NCT02654717. Trial registration: ClinicalTrials.gov identifier: NCT03116698. Trial registration: ClinicalTrials.gov identifier: NCT03538951. Trial registration: ClinicalTrials.gov identifier: NCT02844777. Trial registration: ClinicalTrials.gov identifier: NCT02085395. Trial registration: ClinicalTrials.gov identifier: NCT00786994. Trial registration: ClinicalTrials.gov identifier: NCT03684772. Trial registration: ClinicalTrials.gov identifier: NCT02278861. Trial registration: ClinicalTrials.gov identifier: NCT00021294. Trial registration: ClinicalTrials.gov identifier: NCT00608634. Trial registration: ClinicalTrials.gov identifier: NCT00089180. Trial registration: ClinicalTrials.gov identifier: NCT03210740. Trial registration: ClinicalTrials.gov identifier: NCT00005097.